The Philippines and the International Monetary Fund negotiations on petroleum and imports : toward a theory of negotiation - Faulve-Montojo, Kenneth (Lexington Books, 2018)
"Examines the Philippine-International Monetary Fund negotiations on petroleum and imports from 1984 to 1994. It develops a midrange theory with which to examine country-IMF negotiations"--